Seismic Velocity Variations in a 3D Martian Mantle: Implications for the InSight Measurements. Issue 6 (17th June 2021) - Plesa, A.‐C.; Bozdağ, E.; Rivoldini, A.; Knapmeyer, M.; McLennan, S. M.; Padovan, S.; Tosi, N.; Breuer, D.; Peter, D.; Stähler, S.; Wieczorek, M. A.; van Driel, M.; et al.
Abstract: We use a large data set of 3D thermal evolution models to predict the distribution of present‐day seismic velocities in the Martian interior. Our models show a difference between maximum and minimum S wave velocity of up to 10% either below the crust, where thermal variations are largest, or at the depth of the olivine to wadsleyite phase transition, located at around 1, 000–1, 200 km depth. Models with thick lithospheres on average have weak low‐velocity zones that extend deeper than 400 km and seismic velocity variations in the uppermost 400–600 km that closely follow the crustal thickness pattern. For these cases, the crust contains more than half of the total amount of heat‐producing elements. Models with limited crustal heat production have thinner lithospheres and shallower but prominent low‐velocity zones that are incompatible with Interior exploration using Seismic Investigations, Geodesy and Heat Transport (InSight) observations. Seismic events suggested to originate in Cerberus Fossae indicate the absence of S wave shadow zones in 25°–30° epicentral distance. This result is compatible with previous best fit models that require a large average lithospheric thickness and a crust containing more than half of the bulk amount of heat‐producing elements to be compatible with geological and geophysical constraints. Ongoing and future InSight measurements that will determine the existence of a weak low‐velocity zone will directly bear on the crustal heat production. Plain Language Summary: The crustal thickness variations and the crustal enrichment in heat‐producing elements directly affect the thermal state of the lithosphere and in turn the distribution of seismic velocities in the interior of Mars. Thermal evolution models in a 3D geometry with a crust that contains more than half of the total radioactive heat production show large variations of the seismic velocities in the lithosphere. These models are characterized by a weak low‐velocity zone that extends locally to depths larger than 400 km and a seismic velocity pattern similar to the crustal thickness pattern down to 600 km depth. Models, with limited crustal heat production, and hence higher mantle heat production, lead to a thinner lithosphere that results in shallower but more prominent low‐velocity zones. The latter produce S wave shadow zones that are incompatible with clear S ‐phase arrivals for events located close to Cerberus Fossae. The absence of S wave shadow zones between the Interior exploration using Seismic Investigations, Geodesy and Heat Transport (InSight) landing site and Cerberus Fossae is in line with other geological and geophysical constraints that require a large fraction of heat‐producing elements to be located in the Martian crust. Future InSight measurements will put further constraints on the distribution of heat‐producing elements in the Martian interior. Key Points: Models show up to 10% difference between maximum and minimum S wave velocity either below the crust or at the depth of phase transitions The seismic velocity pattern in the lithosphere correlates with the crustal thickness dichotomy and can extend to depths >400 km Models with a crust containing <20% of the total heat production show shadow zones that are incompatible with current seismic observations